Cellulosic materials as natural fillers in starch-containing matrix-based films: a review - Gutiérrez, Tomy J.; Alvarez, Vera A. (Polymer bulletin (Berlin, Germany), 2017)
In this work, the different cellulosic materials, namely cellulose and lignin are analyzed. In addition, the starch-containing matrices (isolated starch and flour) reinforced with cellulosic materials to be used in packaging applications are described. Many efforts have been exerted to develop biopackaging based on renewable polymers, since these could reduce the environmental impact caused by petrochemical resources. Special attention has had the starch as macromolecule for forming biodegradable packaging. For these reasons, shall also be subject of this review the effect of each type of cellulosic material on the starch-containing matrix-based thermoplastic materials. In this manner, this review contains a description of films based on starch-containing matrices and biocomposites, and then has a review of cellulosic material-based fillers. In the same way, this review contains an analysis of the works carried out on starch-containing matrices reinforced with cellulose and lignin. Finally, the manufacturing processes of starch/cellulose composites are provided as well as the conclusions and the outlook for future works.